2020
DOI: 10.1101/2020.03.21.001867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A molecular mechanism for LINC complex branching by structurally diverse SUN-KASH 6:6 assemblies

Abstract: The LINC complex mechanically couples cytoskeletal and nuclear components across the nuclear envelope to fulfil a myriad of cellular functions, including nuclear shape and positioning, hearing and meiotic chromosome movements. The canonical model of the LINC complex is of individual linear nucleocytoskeletal linkages provided by 3:3 interactions between SUN and KASH proteins. Here, we provide crystallographic and biophysical evidence that SUN-KASH is a constitutive 6:6 complex in which two SUN trimers interact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Surprisingly, this 6:6 assembly was also observed with SUN1:KASH1 complex. Thus, it can be concluded that SUN-KASH complexes are rather forming a network of interacting oligomers instead of the current linear model [41]. KASH1 is a large KASH domain protein with a molecular weight of approximately 1000 kDa.…”
Section: Kash Proteinsmentioning
confidence: 93%
See 1 more Smart Citation
“…Surprisingly, this 6:6 assembly was also observed with SUN1:KASH1 complex. Thus, it can be concluded that SUN-KASH complexes are rather forming a network of interacting oligomers instead of the current linear model [41]. KASH1 is a large KASH domain protein with a molecular weight of approximately 1000 kDa.…”
Section: Kash Proteinsmentioning
confidence: 93%
“…This was proposed for LINC complexes consisting of SUN1, KASH1, and KASH2 based on the X-ray crystallographic analysis [28,31]. However, the assembly of LINC complexes containing KASH4 or KASH5 interacting with SUN1, turned out to form a complex net of 6:6 hetero-oligomeric structures that are in fact 3:3 hetero-hexamers that interact "back-to-back" with one another in the PNS [41]. Surprisingly, this 6:6 assembly was also observed with SUN1:KASH1 complex.…”
Section: Kash Proteinsmentioning
confidence: 99%